Non-Nodal CD5-Negative Mantle Cell Lymphoma with Secondary TP53 Deletion - Robert K. McCall; Changlee S. Pang; Mark J. Pettenati (Case Reports in Hematology)
Mantle cell lymphoma is a non-Hodgkin lymphoproliferative neoplasm with several clinical and morphologic variants linked, primarily, through genetic derangement of the cyclin D1 locus. Aberrant phenotypes have been described, though prognostic data in such cohorts are limited due to a paucity of cases. We report a case of mantle cell lymphoma with non-nodal clinical presentation, aberrant loss of CD5 expression, and concomitant cytogenetic deletion of 17p. While non-nodal disease is often associated with an improved prognosis in mantle cell lymphoma, this 67-year-old patient experienced a more challenging clinical course with a poor initial response to chemotherapy. Therefore, this case may represent a type of non-nodal mantle cell lymphoma with a prognosis similar to that of classical cases due to the additional phenotypic and genetic alterations found in this patient.